El desarrollo de las habilidades sensoriales en los niños de inicial 1 de la unidad educativa “Gabriela Mistral” - Cruz Arrobo, Leydi Vanessa (2023)
The research responds to the following problem: How are sensory skills developed in the children of Initial 1 of the “Gabriela Mistral” Educational Unit? For this reason, the objective was: To diagnose the development of sensory skills in the children of Initial I of the "Gabriela Mistral" Educational Unit. The qualitative approach was the methodology used to guide this work, with the direction of the inductive method, for the analysis and interpretation of the results descriptive, documentary and field research were used. As data collection techniques were used the interview to a teacher, in addition to a survey applied to parents and an observation sheet to 5 children. The results of the investigation according to the interview of 5 questions was found that the children are still in the process of learning because at this age it is time to strengthen the development of sensory skills. The survey of 5 to 7 questions directed to 5 parents show that they rarely apply activities that help the development of sensory skills; according to the observation sheet, it showed that 3 indicators of 5, are in the process of developing sensory skills according to the age of 2-3 years. In conclusion, it is evident that there is a need to strengthen the teaching-learning process with activities and strategies that help the development of sensory skills.